Swine flu (H1N1) pandemic strain-09 PDM: A recent outbreak in northern India - Vinita Choudhary; Chetan Choudhary; Ayushi Sharma; Vinod Kumar Sharma; Pushpendra Saraswat (Journal of Applied Pharmaceutical Research, 2022)
Objective: To Identify molecular characterization of swine flu (H1N1) pdm 09 and seasonal flu (influenza A). Materials and methods: NP/OP Swab specimen of 142 patients were collected aseptically in VTM. Nucleic Acid was extracted manually and was processed in Real-Time PCR for identification of swine flu (H1N1) 09 pdm and seasonal flu (inf A). Results: In this study, 142 patients presented with signs and symptoms of Flu like illness patients and were tested by Real-time PCR. Out of total 32 (22.53%) positive specimens, 18(56.25%) were positive swine flu(H1N1) 09 pdm and 14(43.73%) were positive seasonal flu (inf A). Conclusion: We report a tiny outbreak of 18 swine flu (H1N1) 09 pdm and 14 seasonal flu cases in our hospital, from Jan 2022 to June 2022. The outbreak involved persons of all age groups, but it mostly affected paediatric age group.